Secondary battery and preparation method thereof, energy storage system and electric equipment

By using Fe-N-C to coat MoS2 material in the positive electrode sheet of the lithium-ion battery, the problem of large DC internal resistance of the lithium-ion battery is solved, and the conductivity and rate performance of the battery are improved.

CN120089813AActive Publication Date: 2025-06-03ZHEJIANG JINKO ENERGY STORAGE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510537278.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-06-03
Estimated Expiration
2045-04-25

AI Technical Summary

Technical Problem

The DC internal resistance of existing lithium-ion batteries is relatively large, which affects the battery's energy efficiency, cycle life and safety.

Method used

The synthesis reaction was carried out by mixing the molybdenum source, sulfur source, polyvinylpyrrolidone and water to prepare a layered structure, and then the Fe-N-C coated MoS2 material was formed in the hydrothermal reaction, and the Fe-N-C coated MoS2 material was obtained by calcining treatment, and added to the positive electrode sheet to reduce the internal resistance of the battery.

Benefits of technology

The conductivity and ion transmission performance of the positive electrode sheet are improved, the internal resistance of the secondary battery is reduced, and the rate performance of the secondary battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120089813A_ABST
    Figure CN120089813A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and a preparation method thereof, an energy storage system and electric equipment, and relates to the technical field of energy storage. The preparation method comprises the following steps: mixing a molybdenum source, a sulfur source, polyvinyl pyrrolidone and water, and carrying out a synthetic reaction to obtain MoS2; the preparation method comprises the following steps: mixing raw materials including MoS2, an iron source, imidazole, benzimidazole and an organic solvent, sequentially carrying out hydrothermal reaction and calcination treatment to obtain a Fe-N-C coated MoS2 material, and sequentially mixing, coating and rolling the Fe-N-C coated MoS2 material with a positive active material, a conductive agent and a binder to obtain a positive plate; preparing the positive plate, the diaphragm and the negative plate into a naked battery cell, assembling the naked battery cell with a shell and a top cover, and then injecting electrolyte to obtain the secondary battery; the molar ratio of the MoS2 to the iron source to the imidazole to the benzimidazole is (0.01-1): (0.02-0.2): (0.25-10): (0.05-2). The secondary battery provided by the invention has relatively low direct-current internal resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage, and in particular, to a secondary battery, a preparation method thereof, an energy storage system, and an electrical device. Background Art

[0002] Lithium-ion batteries are widely used in fields such as electric vehicles, energy storage, and consumer electronics. During the charging process, lithium ions are removed from the positive electrode material, transferred through the electrolyte to the negative electrode, and embedded in the negative electrode carbon material; at the same time, electrons are released from the positive electrode and reach the negative electrode through the external circuit to maintain the balance of the chemical reaction. During the discharging process, lithium ions are removed from the negative electrode, reach the positive electrode through the electrolyte, and at the same time the negative electrode releases electrons, which reach the positive electrode through the external circuit to provide energy for the outside world. During the charging and discharging process of the battery, the obstacles encountered by electrons and ions are collectively referred to as the DC internal resistance. The conductivity of the positive electrode material directly affects the DC internal resistance, and further affects the energy efficiency, cycle life, and safety of the battery. At present, lithium batteries usually use conductive carbon black and graphene / carbon nanotubes to reduce the resistance of the positive electrode sheet, reduce the DC internal resistance, and improve the performance of the battery cell, but the improvement effect is not ideal enough. Summary of the Invention

[0003] The main object of the present invention is to provide a secondary battery, a preparation method thereof, an energy storage system, and an electrical device to solve the problem of large DC internal resistance of the secondary battery in the prior art.

[0004] To achieve the above object, according to one aspect of the present invention, a preparation method of a secondary battery is provided, including: S1, mixing a molybdenum source, a sulfur source, polyvinylpyrrolidone, and water, and then performing a synthesis reaction to obtain MoS 2 ; S2, mixing raw materials including MoS 2 , an iron source, imidazole, benzimidazole, and an organic solvent, then performing a hydrothermal reaction, and then performing a calcination treatment under a protective gas to obtain an Fe-N-C-coated MoS 2 material; S3, mixing, coating, and rolling an Fe-N-C-coated MoS 2 material, a positive electrode active material, a conductive agent, and a binder in sequence to obtain a positive electrode sheet; S4, manufacturing a bare battery cell from the positive electrode sheet, a separator, and a negative electrode sheet, assembling the bare battery cell with a housing and a top cover, and then injecting an electrolyte to obtain a secondary battery; wherein, the molar ratio of MoS 2 , the iron source, imidazole, and benzimidazole is (0.01~1):(0.02~0.2):(0.25~10):(0.05~2).

[0005] Further, the temperature of the above hydrothermal reaction is 140 to 180 °C; and / or, the time of the hydrothermal reaction is 24 to 28 h; and / or, the heating rate of the calcination treatment is 2 to 3 °C / min; and / or, the temperature of the calcination treatment is 650 to 750 °C; and / or, the heat preservation time of the calcination treatment is 2 to 3 h.

[0006] Further, the mass ratio of the above Fe-N-C coated MoS 2 material, the cathode active material, the conductive agent and the binder is (0.3 to 1.2):(94.3 to 98.2):(0.5 to 1.5):(1 to 3); and / or, the iron source is selected from any one or more of Fe(NO 3 ) 3 ·6H 2 O, FeCl 3 ·6H 2 O and FeSO 4 ·7H 2 O; and / or, the organic solvent is selected from any one or more of N,N-dimethylformamide, acetonitrile and ethanol.

[0007] Further, the molar ratio of the above molybdenum source, sulfur source and polyvinylpyrrolidone is (0.3 to 1):(4 to 8):(0.003 to 0.01); and / or, the temperature of the synthesis reaction is 210 to 220 °C; and / or, the time of the synthesis reaction is 12 to 24 h.

[0008] Further, the number average molecular weight of the above polyvinylpyrrolidone is 10000 to 60000 Da; and / or, the molybdenum source is selected from any one or more of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, Na 2 MoO 4 ·2H 2 O and (NH 4 ) 2 MoS 4 ; and / or, the sulfur source is selected from any one or more of NH 2 CSNH 2 , C 2 H 5 NS and C 3 H 7 NO 2 S.

[0009] According to another aspect of the present invention, a secondary battery is provided, including a positive electrode sheet, a separator, an electrolyte and a negative electrode sheet. The positive electrode sheet includes a current collector and a positive electrode active layer, and the material of the positive electrode active layer includes Fe-N-C coated MoS2 Materials, a cathode active material, a conductive agent, a binder; wherein, Fe-N-C coated MoS 2 The material is distributed on the surface of the cathode active material; Fe-N-C coated MoS 2 In the material, MoS 2 The mass ratio of MoS to Fe-N-C is 1:(0.2 - 1), and the molar ratio of Fe element, N element and C element in Fe-N-C is (1 - 2):(2 - 4):(50 - 100). The structure of MoS 2 is a layered structure, and the structure of Fe-N-C is a porous structure.

[0010] Furthermore, the mass ratio of the above-mentioned Fe-N-C coated MoS 2 material, the cathode active material, the conductive agent and the binder is (0.3 - 1.2):(94.3 - 98.2):(0.5 - 1.5):(1 - 3).

[0011] Furthermore, the powder resistivity of the above-mentioned Fe-N-C coated MoS 2 material is 10 -2 ~1 Ω·cm; and / or, the average pore diameter of the Fe-N-C coated MoS 2 material is 2 - 20 nm; and / or, the porosity of the Fe-N-C coated MoS 2 material is 50 - 70%.

[0012] According to another aspect of the present invention, an energy storage system is provided, including a unit cell, and the unit cell is a secondary battery prepared by the preparation method of the aforementioned secondary battery or the aforementioned secondary battery.

[0013] According to another aspect of the present invention, an electrical device is provided, including the aforementioned energy storage system, and the energy storage system is used to provide power for the electrical device.

[0014] Applying the technical solution of the present application, the beneficial effects of the present application are as follows: In S1 of the present application, a molybdenum source, a sulfur source, polyvinylpyrrolidone and water are mixed and then subjected to a synthesis reaction. The addition of polyvinylpyrrolidone helps to prepare MoS with a layered structure 2 . In S2, the obtained MoS with a layered structure 2 , a iron source, imidazole, benzimidazole and an organic solvent are mixed and then subjected to a hydrothermal reaction, and the molar ratio of MoS 2 , the iron source, imidazole and benzimidazole is controlled within the above range, which helps to in-situ grow a iron-based metal-organic framework material on the surface of MoS 2 . After that, a calcination treatment is carried out to obtain the Fe-N-C coated MoS 2 material. Compared with directly mixing MoS 2Compared with the case of directly mixing with the iron-based metal-organic framework material and then performing calcination treatment, in-situ growth helps to improve the bonding force between MoS 2 and Fe-N-C, thereby helping to improve the conductivity between MoS 2 and Fe-N-C. Fe-N-C has high conductivity, and the coating of Fe-N-C on the surface of MoS 2 helps to improve the conductivity of MoS 2 . The layered structure of MoS 2 helps to provide channels for rapid ion insertion and extraction, and the Fe-N-C formed from the iron-based metal-organic framework material has a porous structure, which is beneficial to the penetration of the electrolyte and ion diffusion. Adding the Fe-N-C-coated MoS 2 material to the positive electrode sheet helps to improve the conductivity of the positive electrode sheet and improve the ion transport performance of the positive electrode sheet. Assembling the positive electrode sheet into a secondary battery helps to reduce the internal resistance of the secondary battery, thereby helping to improve the rate performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The accompanying drawings forming a part of this application are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation to the present invention. In the drawings:

[0016] Figure 1 Shows the process flow chart of the preparation of the secondary battery of this application. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0017] It should be noted that, without conflict, the embodiments in this application and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the drawings and in combination with the embodiments.

[0018] As analyzed in the background art of this application, for the problem of the large DC internal resistance of secondary batteries in the prior art, in order to solve this problem, this application provides a secondary battery, its preparation method, energy storage system, and electrical equipment.

[0019] In a typical embodiment of this application, a preparation method of a secondary battery is provided. As Figure 1 shown, it includes: S1, mixing a molybdenum source, a sulfur source, polyvinylpyrrolidone, and water and then performing a synthesis reaction to obtain MoS 2 ; S2, mixing raw materials including MoS 2 , an iron source, imidazole, benzimidazole, and an organic solvent, then performing a hydrothermal reaction, and then performing a calcination treatment under a protective gas to obtain an Fe-N-C-coated MoS 2 material; S3, the Fe-N-C-coated MoS 2The materials, the cathode active material, the conductive agent, and the binder are mixed, coated, and roll-pressed in sequence to obtain a cathode sheet; S4, the cathode sheet, the separator, and the anode sheet are made into a bare battery cell, the bare battery cell is assembled with the casing and the top cover, and then the electrolyte is injected to obtain a secondary battery; wherein, the molar ratio of MoS 2 , the iron source, imidazole, and benzimidazole is (0.01~1):(0.02~0.2):(0.25~10):(0.05~2).

[0020] In S1 of the present application, the molybdenum source, the sulfur source, polyvinylpyrrolidone, and water are mixed and then subjected to a synthesis reaction. The addition of polyvinylpyrrolidone helps to prepare MoS with a layered structure 2 . In S2, the obtained MoS with a layered structure 2 , the iron source, imidazole, benzimidazole, and the raw materials of the organic solvent are mixed and then subjected to a hydrothermal reaction, and the molar ratio of MoS 2 , the iron source, imidazole, and benzimidazole is controlled within the above range, which helps to in-situ grow and form an iron-based metal-organic framework material on the surface of MoS 2 . After that, a calcination treatment is carried out to obtain an Fe-N-C-coated MoS 2 material. Compared with directly mixing MoS 2 with the iron-based metal-organic framework material and then carrying out a calcination treatment, the in-situ growth helps to improve the binding force between MoS 2 and Fe-N-C, thereby helping to improve the conductivity between MoS 2 and Fe-N-C. Fe-N-C has high conductivity, and the Fe-N-C coating on the surface of MoS 2 helps to improve the conductivity of MoS 2 . The layered structure of MoS 2 helps to provide channels for rapid ion insertion and extraction, and the Fe-N-C formed from the iron-based metal-organic framework material has a porous structure, which is beneficial to the penetration of the electrolyte and ion diffusion. Adding the Fe-N-C-coated MoS 2 material to the cathode sheet helps to improve the conductivity of the cathode sheet and improve the ion transport performance of the cathode sheet. Assembling the cathode sheet into a secondary battery helps to reduce the internal resistance of the secondary battery, thereby helping to improve the rate performance of the secondary battery.

[0021] It should be noted that the cathode active material, the separator, the anode sheet, and the electrolyte of the present application can all be obtained by purchase or through the prior art.

[0022] Including but not limited to, the above conductive agent is selected from any one or more of Super-P, carbon nanotubes, graphene, and carbon fibers; the above binder is selected from any one or more of polyvinylidene fluoride, polyvinylidene difluoride, styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid.

[0023] The function of the protective gas is to reduce the contact between the Fe-N-C coated MoS 2 material and oxygen in the air. Including but not limited to, the above-mentioned protective gas is selected from any one or more of nitrogen, helium and argon.

[0024] In order to improve the uniformity of the dispersion of the Fe-N-C coated MoS 2 material on the surface of the positive electrode active material, thereby further improving the conductivity and ion transport performance of the positive electrode sheet. In one embodiment of the present application, in the above S3, first mix the positive electrode active material, the conductive agent and the binder, and then add the Fe-N-C coated MoS 2 material and continue to mix to obtain a mixed material, and successively coat and roll the mixed material to obtain a positive electrode sheet.

[0025] In one embodiment of the present application, the temperature of the hydrothermal reaction is 140~180°C; and / or, the time of the hydrothermal reaction is 24~28h; and / or, the heating rate of the calcination treatment is 2~3°C / min; and / or, the temperature of the calcination treatment is 650~750°C; and / or, the heat preservation time of the calcination treatment is 2~3h.

[0026] Controlling the temperature and time of the hydrothermal reaction within the above range helps to promote the reaction between MoS 2 and the Fe source, imidazole and benzimidazole without damaging the material, and form a uniform and stable iron-based metal-organic framework material coated with MoS 2 material. Controlling the heating rate of the calcination treatment within the above range helps to reduce the stress generated inside the material, thereby helping to form a stable Fe-N-C coated MoS 2 material. Controlling the temperature and time of the calcination treatment within the above range helps to promote the carbonization of the iron-based metal-organic framework material to form a Fe-N-C coating layer with appropriate thickness, pore size and porosity, and helps to improve the Fe-N-C coated MoS 2 material purity while improving the structural stability and conductivity of the Fe-N-C coated MoS 2 material, thereby helping to further improve the conductivity and ion transport performance of the positive electrode sheet, and further helping to reduce the internal resistance of the secondary battery.

[0027] In one embodiment of the present application, the mass ratio of the above Fe-N-C coated MoS 2 material, positive electrode active material, conductive agent and binder is (0.3~1.2):(94.3~98.2):(0.5~1.5):(1~3); and / or, the iron source is selected from Fe(NO 3 ) 3 ·6H 2O, FeCl 3 ·6H 2 O and FeSO 4 ·7H 2 O, or any one or more of them; and / or, the organic solvent is selected from any one or more of N,N-dimethylformamide, acetonitrile and ethanol.

[0028] The Fe-N-C coated MoS 2 material provides an additional conductive path and ion transport channels, the positive electrode active material provides energy storage, the addition of the conductive agent helps to improve the electron conduction ability of the positive electrode material, and the presence of the binder helps to make the electrode material have good contact with the current collector, and improve the mechanical stability of the positive electrode sheet. Controlling the mass ratio of the Fe-N-C coated MoS 2 material, the positive electrode active material, the conductive agent and the binder within the above range helps to improve the mutual synergistic effect between the components, thereby helping to reduce the internal resistance of the secondary battery and improve the capacity, rate performance, cycle stability and safety of the secondary battery.

[0029] In an embodiment of the present application, the molar ratio of the above molybdenum source, sulfur source and polyvinylpyrrolidone is (0.3~1):(4~8):(0.003~0.01); and / or, the temperature of the synthesis reaction is 210~220 °C; and / or, the time of the synthesis reaction is 12~24 h.

[0030] Controlling the molar ratio of the molybdenum source, sulfur source and polyvinylpyrrolidone within the above range helps to promote the formation of the MoS 2 layered structure, making it have good ion insertion and extraction channels. Controlling the temperature and time of the synthesis reaction within the above range helps to improve the integrity and stability of the MoS 2 layered structure, thereby helping to improve the ion transport efficiency of the Fe-N-C coated MoS 2 material, and further helping to reduce the internal resistance of the secondary battery and improve the rate performance of the secondary battery.

[0031] In an embodiment of the present application, the number average molecular weight of the above polyvinylpyrrolidone is 10000~60000 Da, specifically it can be 10000 Da, 20000 Da, 30000 Da, 40000 Da, 50000 Da, 60000 Da and the range values between any two values; and / or, the molybdenum source is selected from (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, Na 2 MoO 4 ·2H 2 O and (NH4 ) 2 MoS 4 Any one or more of; and / or, the sulfur source is selected from NH 2 CSNH 2 、C 2 H 5 NS and C 3 H 7 NO 2 Any one or more of S.

[0032] Controlling the number-average molecular weight of polyvinylpyrrolidone within the above range helps to provide better dispersion and stability for the synthesis reaction system and helps to reduce the aggregation of MoS 2 ; on the other hand, it helps to control the formation of a layered structure of MoS 2 , thereby helping to further improve the conductivity, ion transport efficiency and stability of the Fe-N-C coated MoS 2 material. Controlling the types of molybdenum source and sulfur source within the above range helps to improve the interaction between the two and promote the formation of a layered structure of MoS 2 , thereby helping to further improve the conductivity, ion transport efficiency and stability of the Fe-N-C coated MoS 2 material.

[0033] In another typical embodiment of the present application, a secondary battery is provided, including a positive electrode sheet, a separator, an electrolyte and a negative electrode sheet. The positive electrode sheet includes a current collector and a positive electrode active layer. The material of the positive electrode active layer includes Fe-N-C coated MoS 2 material, a positive electrode active material, a conductive agent, and a binder; wherein, the Fe-N-C coated MoS 2 material is distributed on the surface of the positive electrode active material; in the Fe-N-C coated MoS 2 material, the mass ratio of MoS 2 to Fe-N-C is 1:(0.2~1), specifically 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 and the range values between any two ratios. The molar ratio of Fe element, N element and C element in Fe-N-C is (1~2):(2~4):(50~100). The structure of MoS 2 is a layered structure, and the structure of Fe-N-C is a porous structure.

[0034] Fe-N-C has high conductivity. Coating Fe-N-C on the surface of MoS 2 helps to improve the conductivity of MoS 2 , and MoS 2The layered structure helps to provide channels for rapid ion insertion and extraction, and Fe-N-C has a porous structure, which is beneficial to the penetration of the electrolyte and ion diffusion. Since the above-mentioned positive electrode sheet contains Fe-N-C coated on MoS 2 , therefore, the positive electrode sheet has high electrical conductivity and ion transport performance. Having this positive electrode sheet in the secondary battery helps to reduce the internal resistance of the secondary battery, thereby helping to improve the rate performance of the secondary battery.

[0035] In an embodiment of the present application, the mass ratio of the above Fe-N-C coated MoS 2 material, positive electrode active material, conductive agent and binder is (0.3~1.2):(94.3~98.2):(0.5~1.5):(1~3).

[0036] The Fe-N-C coated MoS 2 material has high electrical conductivity and ion transport performance. Controlling the mass ratio of the Fe-N-C coated MoS 2 material, positive electrode active material, conductive agent and binder within the above range helps to improve the interaction between the components, and improves the electrical conductivity and ion transport performance of the positive electrode sheet without reducing the structural stability of the positive electrode sheet, thereby helping to reduce the internal resistance of the secondary battery and improve the capacity, rate performance, cycle stability and safety of the secondary battery.

[0037] In an embodiment of the present application, the powder resistivity of the above Fe-N-C coated MoS 2 material is 10 -2 ~1 Ω·cm; and / or, the average pore diameter of the Fe-N-C coated MoS 2 material is 2~20 nm; and / or, the porosity of the Fe-N-C coated MoS 2 material is 50~70%.

[0038] The Fe-N-C coated MoS 2 material with the above powder resistivity is located on the surface of the positive electrode active material, which helps to improve the electrical conductivity of the positive electrode sheet, thereby helping to reduce the internal resistance of the secondary battery and improve the capacity, rate performance, cycle stability and safety of the secondary battery. Controlling the average pore diameter and porosity of the Fe-N-C coated MoS 2 material within the above range helps to promote the penetration of the electrolyte and the diffusion of ions, shorten the ion transport path, thereby helping to accelerate the ion diffusion speed and improve the charge and discharge rate of the secondary battery.

[0039] In an embodiment of the present application, the thickness of the Fe-N-C coating layer in the above Fe-N-C coated MoS 2 material is 5~20 nm.

[0040] Controlling Fe-N-C Coated MoS 2 When the thickness of the Fe-N-C coating layer in the material is within the above range, on the one hand, it helps to reduce the contact resistance between the MoS 2 material and the current collector, thereby helping to reduce the internal resistance of the entire secondary battery; on the other hand, it helps to improve the ion transport efficiency while enhancing the stability of the Fe-N-C coating layer.

[0041] In an embodiment of the present application, the layered structure of the above-mentioned MoS 2 is formed by stacking MoS 2 nanosheets. The average thickness of the MoS 2 nanosheets is 1.2 - 4.0 nm, and the average planar diameter of the MoS 2 nanosheets is 100 - 300 nm.

[0042] Controlling the thickness and planar diameter of the MoS 2 nanosheets within the above range, on the one hand, helps to shorten the ion transport path, thereby helping to reduce the internal resistance of the secondary battery, and further helping to improve the rate performance of the secondary battery; on the other hand, it helps to increase the active contact area, enabling ions to contact the MoS 2 material more fully, thereby helping to increase the specific capacity of the positive electrode sheet and further helping to improve the energy density of the secondary battery.

[0043] In an embodiment of the present application, the resistivity of the above-mentioned positive electrode sheet is 207.4412 - 248.7414 Ω·mm, and the conductivity is 0.004232 - 0.004732 S / mm.

[0044] In another typical embodiment of the present application, an energy storage system is provided, including a unit cell, and the unit cell is a secondary battery prepared by the preparation method of the foregoing secondary battery or the foregoing secondary battery.

[0045] Since the above-mentioned energy storage system contains the secondary battery of the present application, therefore, the energy storage system has high rate performance and cycle stability.

[0046] In another typical embodiment of the present application, an electrical device is provided, including the foregoing energy storage system, and the energy storage system is used to provide power for the electrical device.

[0047] Since the energy storage system of the above-mentioned electrical device contains the secondary battery of the present application, therefore, the electrical device has high rate performance, cycle stability and safety.

[0048] The beneficial effects of the present application will be further described below in conjunction with embodiments.

[0049] Example 1

[0050] The preparation process flow of the secondary battery is as Figure 1 shown. Specifically, 0.03 M of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, 0.4 M of NH 2 CSNH 2 , and 0.3 mM of polyvinylpyrrolidone (number-average molecular weight is 40000 Da) are dissolved in 60 mL of deionized water, and magnetically stirred for 30 min to form a homogeneous solution; the solution is transferred to a 100 mL Teflon liner, loaded into a reaction kettle, and synthesized at 210 °C for 24 h; after cooling to room temperature, the obtained product is centrifuged, washed several times with water and ethanol, and vacuum dried at 50 °C for 12 h to obtain layered MoS 2 , and the layered structure is formed by stacking MoS 2 nanosheets. The average thickness of the MoS 2 nanosheets is 2.0 nm, and the average planar diameter of the MoS 2 nanosheets is 200 nm; 0.02 M of Fe(NO 3 ) 3 ·6H 2 O, 0.25 M of imidazole, 0.05 M of benzimidazole, and 0.01 M of MoS 2 are dissolved in 60 mL of N,N-dimethylformamide, magnetically stirred for 30 min, the mixture is transferred to a 100 mL Teflon liner, loaded into a reaction kettle, and hydrothermally reacted at 140 °C for 24 h. After natural cooling, the obtained liquid is centrifuged and washed 3 times with ethanol, and dried to obtain an iron-based metal-organic framework material-coated MoS 2 . Then, it is calcined at 650 °C for 2 h under an argon atmosphere with a heating rate of 2 °C / min to obtain an Fe-N-C-coated MoS 2 material, and the powder resistivity is 10 -1 Ω·cm; among them, the mass ratio of MoS 2 to Fe-N-C is 1:0.6, the molar ratio of Fe element, N element, and C element in Fe-N-C is 2:2:50, the average pore diameter of the Fe-N-C-coated MoS 2 material is 10 nm, the porosity is 60%, and the thickness of the Fe-N-C coating layer in the Fe-N-C-coated MoS 2 material is 12 nm.

[0051] First, lithium iron phosphate, Super-P, and polyvinylidene fluoride are mixed, and then the above-prepared Fe-N-C-coated MoS 2 material is added and mixed continuously. The Fe-N-C-coated MoS2 The mass ratio of the materials, lithium iron phosphate, Super-P and polyvinylidene fluoride is 1.2:96.1:0.7:2. After coating, rolling, slitting, tab forming and blanking, the positive electrode sheet is obtained. After laminating the positive electrode sheet, the graphite negative electrode sheet and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation and air extraction and edge sealing to obtain a secondary battery.

[0052] Example 2

[0053] The difference from Example 1 is that the molar ratio of MoS 2 , Fe(NO 3 ) 3 ·6H 2 O, imidazole and benzimidazole is 0.01:0.2:10:2, and finally Fe-N-C coated MoS 2 material is obtained, with a powder resistivity of 10 -2 Ω·cm. Among them, the mass ratio of MoS 2 to Fe-N-C is 1:1, and the molar ratio of Fe element, N element and C element in Fe-N-C is 1:4:100. The thickness of the Fe-N-C coating layer in the Fe-N-C coated MoS 2 material is 20 nm.

[0054] First, mix lithium iron phosphate, Super-P and polyvinylidene fluoride, and then add the above-prepared Fe-N-C coated MoS 2 material and continue to mix. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P and polyvinylidene fluoride is 1.2:96.1:0.7:2. After coating, rolling, slitting, tab forming and blanking, the positive electrode sheet is obtained. After laminating the positive electrode sheet, the graphite negative electrode sheet and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation and air extraction and edge sealing to obtain a secondary battery.

[0055] Example 3

[0056] The difference from Example 1 is that the molar ratio of MoS 2 , Fe(NO 3 ) 3 ·6H 2 O, imidazole and benzimidazole is 1:0.02:0.25:0.05, and finally Fe-N-C coated MoS 2 material is obtained, with a powder resistivity of 1 Ω·cm. Among them, the mass ratio of MoS 2 to Fe-N-C is 1:0.2, and the molar ratio of Fe element, N element and C element in Fe-N-C is 2:2:50. The Fe-N-C coated MoS2 The thickness of the Fe-N-C coating layer in the material is 5 nm.

[0057] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the prepared Fe-N-C coated MoS 2 material and continue to mix. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, it is coated, roll-pressed, slit, tab-formed, and sliced to obtain the positive electrode sheet. The positive electrode sheet, graphite negative electrode sheet, and polyethylene separator are laminated into a bare battery cell, and then the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0058] Example 4

[0059] The difference from Example 1 is that the hydrothermal reaction temperature is 180 °C and the hydrothermal reaction time is 28 h. Finally, the Fe-N-C coated MoS 2 material is obtained, and the powder resistivity is 0.08 Ω·cm. Among them, the Fe-N-C coated MoS 2 material has an average pore size of 5 nm and a porosity of 50%. The Fe-N-C coated MoS 2 material has a Fe-N-C coating layer thickness of 15 nm.

[0060] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the prepared Fe-N-C coated MoS 2 material and continue to mix. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, it is coated, roll-pressed, slit, tab-formed, and sliced to obtain the positive electrode sheet. The positive electrode sheet, graphite negative electrode sheet, and polyethylene separator are laminated into a bare battery cell, and then the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0061] Example 5

[0062] The difference from Example 1 is that the hydrothermal reaction temperature is 200 °C and the hydrothermal reaction time is 30 h. Finally, the Fe-N-C coated MoS 2 material is obtained, and the powder resistivity is 0.05 Ω·cm. Among them, the Fe-N-C coated MoS 2 material has an average pore size of 1 nm and a porosity of 45%. The Fe-N-C coated MoS 2 material has a Fe-N-C coating layer thickness of 18 nm.

[0063] Lithium iron phosphate, Super-P, and polyvinylidene fluoride are first mixed, and then the Fe-N-C coated MoS prepared above is added 2 material and continue to mix. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, it is coated, roll-pressed, slit, tab-formed, and sliced to obtain a positive electrode sheet. The positive electrode sheet, graphite negative electrode sheet, and polyethylene separator are laminated into a bare battery cell, and then the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and gas extraction and edge sealing to obtain a secondary battery.

[0064] Example 6

[0065] The difference from Example 1 is that the heating rate of the calcination treatment is 3 °C / min, the temperature of the calcination treatment is 750 °C, and the holding time of the calcination treatment is 3 h. Finally, the Fe-N-C coated MoS 2 material is obtained, and the powder resistivity is 0.12 Ω·cm. Among them, the Fe-N-C coated MoS 2 material has an average pore size of 13 nm and a porosity of 63%. The thickness of the Fe-N-C coating layer in the Fe-N-C coated MoS 2 material is 11 nm.

[0066] Lithium iron phosphate, Super-P, and polyvinylidene fluoride are first mixed, and then the Fe-N-C coated MoS prepared above is added 2 material and continue to mix. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, it is coated, roll-pressed, slit, tab-formed, and sliced to obtain a positive electrode sheet. The positive electrode sheet, graphite negative electrode sheet, and polyethylene separator are laminated into a bare battery cell, and then the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and gas extraction and edge sealing to obtain a secondary battery.

[0067] Example 7

[0068] The difference from Example 1 is that the heating rate of the calcination treatment is 4 °C / min, the temperature of the calcination treatment is 800 °C, and the holding time of the calcination treatment is 4 h. Finally, the Fe-N-C coated MoS 2 material is obtained, and the powder resistivity is 0.09 Ω·cm. Among them, the Fe-N-C coated MoS 2 material has an average pore size of 1.5 nm and a porosity of 48%. The thickness of the Fe-N-C coating layer in the Fe-N-C coated MoS 2 material is 9 nm.

[0069] Mix lithium iron phosphate, Super-P, and polyvinylidene fluoride first, and then add the Fe-N-C coated MoS prepared above 2 material and continue to mix. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. Then, after coating, rolling, slitting, tab forming, and blanking, a positive electrode sheet is obtained. After laminating the positive electrode sheet, the graphite negative electrode sheet, and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0070] Example 8

[0071] The difference from Example 1 is that lithium iron phosphate, Super-P, and polyvinylidene fluoride are mixed first, and then the Fe-N-C coated MoS prepared above 2 material is added and mixing continues. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 0.3:98.2:1.5:3. Then, after coating, rolling, slitting, tab forming, and blanking, a positive electrode sheet is obtained. After laminating the positive electrode sheet, the graphite negative electrode sheet, and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0072] Example 9

[0073] The difference from Example 1 is that lithium iron phosphate, Super-P, and polyvinylidene fluoride are mixed first, and then the Fe-N-C coated MoS prepared above 2 material is added and mixing continues. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 0.1:98.2:1.5:3. Then, after coating, rolling, slitting, tab forming, and blanking, a positive electrode sheet is obtained. After laminating the positive electrode sheet, the graphite negative electrode sheet, and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0074] Example 10

[0075] The difference from Example 1 is that (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, NH 2 CSNH 2The molar ratio with polyvinylpyrrolidone is 0.3:4:0.01, the temperature of the synthesis reaction is 220 °C, and the time of the synthesis reaction is 12 h, obtaining MoS with a layered structure 2 , and the layered structure is formed by stacking MoS 2 nanosheets. The average thickness of the MoS 2 nanosheets is 3 nm, and the average planar diameter of the MoS 2 nanosheets is 250 nm. Using the above-mentioned MoS 2 to prepare the Fe-N-C coated MoS 2 material.

[0076] First, mix lithium iron phosphate, Super-P and polyvinylidene fluoride, and then add the above-prepared Fe-N-C coated MoS 2 material to continue mixing. The mass ratio of the Fe-N-C coated MoS 2 material, lithium iron phosphate, Super-P and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, it goes through processes such as coating, rolling, slitting, tab forming, and sheet cutting to obtain the positive electrode sheet. Stack the positive electrode sheet, graphite negative electrode sheet and polyethylene separator into a bare battery cell, and then successively perform tab welding, encapsulation, liquid injection, formation and air extraction and edge sealing on the bare battery cell to obtain the secondary battery.

[0077] Example 11

[0078] The difference from Example 1 is that the molar ratio of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, NH 2 CSNH 2 and polyvinylpyrrolidone is 0.3:4:0.02, the temperature of the synthesis reaction is 200 °C, and the time of the synthesis reaction is 10 h, obtaining MoS with a layered structure 2 , and the layered structure is formed by stacking MoS 2 nanosheets. The average thickness of the MoS 2 nanosheets is 5 nm, and the average planar diameter of the MoS 2 nanosheets is 350 nm. Using the above-mentioned MoS 2 to prepare the Fe-N-C coated MoS 2 material.

[0079] First, mix lithium iron phosphate, Super-P and polyvinylidene fluoride, and then add the above-prepared Fe-N-C coated MoS 2 material to continue mixing. The mass ratio of the Fe-N-C coated MoS 2The mass ratio of the materials, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, the mixture is coated, roll-pressed, slit, tab-formed, and sliced to obtain the positive electrode sheet. The positive electrode sheet, graphite negative electrode sheet, and polyethylene separator are laminated into a bare battery cell, and then the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and gas extraction and edge sealing to obtain a secondary battery.

[0080] Example 12

[0081] The difference from Example 1 is that the number-average molecular weight of polyvinylpyrrolidone is 10,000 Da, and a layered structure of MoS 2 is obtained. The layered structure is formed by stacking MoS 2 nanosheets. The average thickness of the MoS 2 nanosheets is 1.2 nm, and the average planar diameter of the MoS 2 nanosheets is 100 nm. Using the above MoS 2 , an Fe-N-C-coated MoS 2 material is prepared.

[0082] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the above-prepared Fe-N-C-coated MoS 2 material to continue mixing. The mass ratio of the Fe-N-C-coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, the mixture is coated, roll-pressed, slit, tab-formed, and sliced to obtain the positive electrode sheet. The positive electrode sheet, graphite negative electrode sheet, and polyethylene separator are laminated into a bare battery cell, and then the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and gas extraction and edge sealing to obtain a secondary battery.

[0083] Example 13

[0084] The difference from Example 1 is that the number-average molecular weight of polyvinylpyrrolidone is 60,000 Da, and a layered structure of MoS 2 is obtained. The layered structure is formed by stacking MoS 2 nanosheets. The average thickness of the MoS 2 nanosheets is 4.0 nm, and the average planar diameter of the MoS 2 nanosheets is 300 nm. Using the above MoS 2 , an Fe-N-C-coated MoS 2 material is prepared.

[0085] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the above-prepared Fe-N-C-coated MoS 2 material to continue mixing. The Fe-N-C-coated MoS2 The mass ratio of the materials, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, the positive electrode sheet is obtained through coating, rolling, slitting, tab forming, and blanking. After laminating the positive electrode sheet, the graphite negative electrode sheet, and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0086] Example 14

[0087] The difference from Example 1 is that the number-average molecular weight of polyvinylpyrrolidone is 80,000 Da, and a layered MoS structure is obtained. 2 , and the layered structure is formed by stacking MoS 2 nanosheets. The average thickness of the MoS 2 nanosheets is 4.8 nm, and the average planar diameter of the MoS 2 nanosheets is 360 nm. Using the above MoS 2 , Fe-N-C-coated MoS 2 materials are prepared.

[0088] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the prepared Fe-N-C-coated MoS 2 materials and continue to mix. The mass ratio of the Fe-N-C-coated MoS 2 materials, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, the positive electrode sheet is obtained through coating, rolling, slitting, tab forming, and blanking. After laminating the positive electrode sheet, the graphite negative electrode sheet, and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0089] Comparative Example 1

[0090] The difference from Example 1 is that the addition of the Fe-N-C-coated MoS 2 materials is cancelled. Mix lithium iron phosphate, Super-P, and polyvinylidene fluoride. The mass ratio of lithium iron phosphate, Super-P, and polyvinylidene fluoride is 96.1:0.7:2. After that, the positive electrode sheet is obtained through coating, rolling, slitting, tab forming, and blanking. After laminating the positive electrode sheet, the graphite negative electrode sheet, and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0091] Comparative Example 2

[0092] The difference from Example 1 is that MoS 2 , Fe(NO 3 ) 3·6H 2 The molar ratio of O, imidazole, and benzimidazole is 2:0.02:0.25:0.05, and finally, Fe-N-C-coated MoS 2 material is obtained. The powder resistivity is 1.8 Ω·cm. Among them, the mass ratio of MoS 2 to Fe-N-C is 1:0.11. The molar ratio of Fe element, N element, and C element in Fe-N-C is 2:2:50. The thickness of the Fe-N-C coating layer in the Fe-N-C-coated MoS 2 material is 2 nm.

[0093] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the above-prepared Fe-N-C-coated MoS 2 material to continue mixing. The mass ratio of Fe-N-C-coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, it is coated, roll-pressed, slit, tab-formed, and sliced to obtain a positive electrode sheet. The positive electrode sheet, graphite negative electrode sheet, and polyethylene separator are laminated into a bare battery cell, and then the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0094] Comparative Example 3

[0095] The difference from Example 1 is that the molar ratio of MoS 2 , Fe(NO 3 ) 3 ·6H 2 O, imidazole, and benzimidazole is 0.005:0.2:10:2, and finally, Fe-N-C-coated MoS 2 material is obtained. The powder resistivity is 0.007 Ω·cm. Among them, the mass ratio of MoS 2 to Fe-N-C is 1:2.3. The molar ratio of Fe element, N element, and C element in Fe-N-C is 1:4:100. The thickness of the Fe-N-C coating layer in the Fe-N-C-coated MoS 2 material is 25 nm.

[0096] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the above-prepared Fe-N-C-coated MoS 2 material to continue mixing. The Fe-N-C-coated MoS 2The mass ratio of the materials, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, the positive electrode sheet is obtained through coating, rolling, slitting, tab forming, and blanking. After laminating the positive electrode sheet, the graphite negative electrode sheet, and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and gas extraction and edge sealing to obtain a secondary battery.

[0097] Comparative Example 4

[0098] The difference from Example 1 is that the addition of polyvinylpyrrolidone is cancelled to obtain MoS 2 , and the above-mentioned MoS 2 is used to prepare Fe-N-C-coated MoS 2 material.

[0099] Lithium iron phosphate, Super-P, and polyvinylidene fluoride are first mixed, and then the above-prepared Fe-N-C-coated MoS 2 material is added and the mixture is continued to be mixed. The mass ratio of the Fe-N-C-coated MoS 2 material, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, the positive electrode sheet is obtained through coating, rolling, slitting, tab forming, and blanking. After laminating the positive electrode sheet, the graphite negative electrode sheet, and the polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and gas extraction and edge sealing to obtain a secondary battery.

[0100] Comparative Example 5

[0101] The difference from Example 1 is that the addition of MoS 2 is cancelled, and 0.02 M of Fe(NO 3 ) 3 ·6H 2 O, 0.25 M of imidazole, and 0.05 M of benzimidazole are dissolved in 60 mL of N,N-dimethylformamide, magnetically stirred for 30 min, the mixture is transferred to a 100 mL Teflon liner, loaded into a reaction kettle, and hydrothermally reacted at 140 °C for 24 h. After natural cooling, the obtained liquid is centrifuged and washed with ethanol 3 times, dried to obtain an iron-based metal-organic framework material, and then calcined at 650 °C for 2 h under an argon atmosphere with a heating rate of 2 °C / min to obtain Fe-N-C.

[0102] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the prepared Fe-N-C material above to continue mixing. The mass ratio of Fe-N-C, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, through coating, rolling, slitting, tab forming, and sheet cutting, a positive electrode sheet is obtained. After laminating the positive electrode sheet, graphite negative electrode sheet, and polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0103] Comparative Example 6

[0104] The difference from Example 1 is that the coating of Fe-N-C is cancelled. First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the prepared MoS 2 material above to continue mixing. The mass ratio of MoS 2 , lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, through coating, rolling, slitting, tab forming, and sheet cutting, a positive electrode sheet is obtained. After laminating the positive electrode sheet, graphite negative electrode sheet, and polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0105] Comparative Example 7

[0106] The difference from Example 1 is that the calcination treatment is cancelled. First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the prepared iron-based metal-organic framework material-coated MoS 2 above to continue mixing. The mass ratio of iron-based metal-organic framework material-coated MoS 2 , lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. After that, through coating, rolling, slitting, tab forming, and sheet cutting, a positive electrode sheet is obtained. After laminating the positive electrode sheet, graphite negative electrode sheet, and polyethylene separator into a bare battery cell, the bare battery cell is successively subjected to tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing to obtain a secondary battery.

[0107] Comparative Example 8

[0108] The difference from Example 1 is that the hydrothermal reaction is cancelled. Use 0.02M of Fe(NO 3 ) 3 ·6H 2 O, 0.25M of imidazole, 0.05M of benzimidazole, 0.01M of MoS 2Dissolve it in 60 mL of N,N-dimethylformamide, stir magnetically for 30 min, dry the mixture to obtain a mixed material, and then calcine it at 650 °C for 2 h under an argon atmosphere with a heating rate of 2 °C / min to obtain MoS with Fe, N, and C elements on the surface. 2 Material.

[0109] First, mix lithium iron phosphate, Super-P, and polyvinylidene fluoride, and then add the MoS material with Fe, N, and C elements on the surface prepared above. 2 Material to continue mixing. The mass ratio of the MoS material with Fe, N, and C elements on the surface, lithium iron phosphate, Super-P, and polyvinylidene fluoride is 1.2:96.1:0.7:2. Then, after coating, rolling, slitting, tab forming, and blanking, a positive electrode sheet is obtained. Stack the positive electrode sheet, graphite negative electrode sheet, and polyethylene separator into a bare battery cell, and then successively perform tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing on the bare battery cell to obtain a secondary battery. 2 After coating, rolling, slitting, tab forming, and blanking, a positive electrode sheet is obtained. Stack the positive electrode sheet, graphite negative electrode sheet, and polyethylene separator into a bare battery cell, and then successively perform tab welding, encapsulation, liquid injection, formation, and air extraction and edge sealing on the bare battery cell to obtain a secondary battery.

[0110] Comparative Example 9

[0111] The difference from Example 1 is that the addition of Fe(NO 3 ) 3 ·6H 2 O is cancelled, and finally a secondary battery is obtained.

[0112] Comparative Example 10

[0113] The difference from Example 1 is that the addition of imidazole and benzimidazole is cancelled, and finally a secondary battery is obtained.

[0114] Performance Test

[0115] Test the resistivity and conductivity of the positive electrode sheets prepared in the examples and comparative examples. The test results are shown in Table 1; for the secondary batteries prepared in the examples and comparative examples, at an ambient temperature of 25 °C, test the first discharge specific capacity at 0.5C and the capacity retention rate after 1000 cycles at 0.5C. The test results are shown in Table 1.

[0116] Table 1

[0117]

[0118] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0119] As can be seen from Table 1, in Examples 1 to 3, as the mass of the Fe-N-C coating layer increases, the conductivity of the positive electrode sheet is significantly improved. However, it is not that the larger the mass of the Fe-N-C coating layer, the better. From the data of the first discharge specific capacity and capacity retention rate, it can be seen that the effect of Example 1 is better than that of Examples 2 and 3; from the comparison results of Examples 1, 4, and 5, it can be seen that the hydrothermal reaction temperature has a more obvious effect on the average pore size and porosity of the Fe-N-C coated MoS 2 material. When the hydrothermal reaction temperature is too high, the average pore size and porosity of the Fe-N-C coated MoS 2 material decrease, affecting the lithium ion transport efficiency, so that the first discharge specific capacity and capacity retention rate of Examples 1 and 4 are better than those of Example 5; from the comparison results of Examples 1, 6, and 7, it can be seen that the calcination treatment conditions also have a certain effect on the average pore size and porosity of the Fe-N-C coated MoS 2 material, so that the first discharge specific capacity and capacity retention rate of Examples 1 and 6 are better than those of Example 7; Examples 1, 8, and 9 are to adjust the proportion of the Fe-N-C coated MoS 2 material in the positive electrode material. From the data, it can be seen that the proportion of the Fe-N-C coated MoS 2 material significantly affects the first discharge specific capacity and capacity retention rate of the battery; Examples 1, 10, and 11 control the addition amount of polyvinylpyrrolidone to regulate the thickness and surface diameter of the MoS 2 nanosheets. From the data results, it can be seen that adding an appropriate amount of polyvinylpyrrolidone helps to control the thickness and surface diameter of the MoS 2 nanosheets within an appropriate range, thus helping to improve the first discharge specific capacity and capacity retention rate of the battery; Examples 1, 12 - 14 regulate the thickness and surface diameter of the MoS 2 nanosheets by adjusting the number average molecular weight of polyvinylpyrrolidone. From the data results, it can be seen that polyvinylpyrrolidone with an appropriate number average molecular weight helps to regulate the thickness and surface diameter of the MoS 2 nanosheets to an appropriate range, thus helping to improve the first discharge specific capacity and capacity retention rate of the battery.

[0120] From the test results of Example 1 and Comparative Example 1, it can be seen that by canceling the addition of the Fe-N-C coated MoS 2 material, the resistivity of the positive electrode sheet increases significantly and the conductivity decreases significantly, resulting in the first discharge specific capacity and capacity retention rate of the battery in Comparative Example 1 being significantly lower than those in Example 1; in Comparative Examples 2 and 3, by adjusting the mass ratio of MoS 2 to Fe-N-C, it can be seen that MoS 2A ratio of mass that is either too large or too small compared to that of Fe-N-C is not conducive to improving the initial discharge specific capacity and capacity retention rate of the battery; in Comparative Example 4, the addition of polyvinylpyrrolidone was cancelled, which affected the 2 morphology and structure of MoS 2 , thus affecting the lithium ion transport efficiency, and further significantly decreasing the initial discharge specific capacity and capacity retention rate of the battery; in Comparative Example 5, the addition of MoS 2 was cancelled. Although it had little effect on the resistivity and conductivity of the positive electrode sheet, it affected the lithium ion transport efficiency of the positive electrode sheet, also significantly decreasing the initial discharge specific capacity and capacity retention rate of the battery; in Comparative Example 6, the coating of Fe-N-C was cancelled, significantly affecting the resistivity and conductivity of the positive electrode sheet, thus resulting in poor initial discharge specific capacity and capacity retention rate of the battery; in Comparative Example 7, the calcination treatment was cancelled, and a Fe-N-C coating layer with high conductivity was not formed, seriously affecting the resistivity and conductivity of the positive electrode sheet, thus resulting in a low initial discharge specific capacity and capacity retention rate of the battery; in Comparative Example 8, the hydrothermal reaction was cancelled, and the iron-based metal-organic framework material was not in-situ grown on the surface of MoS 2 , so that a Fe-N-C coating layer with high conductivity could not be formed during the calcination process, resulting in a decrease in the initial discharge specific capacity and capacity retention rate of the battery; in Comparative Example 9, the addition of Fe(NO 3 ) 3 ·6H 2 O was cancelled, and in Comparative Example 10, the addition of imidazole and benzimidazole was cancelled, so that no iron-based metal-organic framework material was formed during the hydrothermal reaction in Comparative Example 9 and Comparative Example 10, so that a Fe-N-C coating layer with high conductivity could not be formed during the calcination process, resulting in a decrease in the initial discharge specific capacity and capacity retention rate of the battery.

[0121] In step S1 of the present application, a molybdenum source, a sulfur source, polyvinylpyrrolidone and water are mixed and then a synthesis reaction is carried out. The addition of polyvinylpyrrolidone helps to prepare MoS 2 with a layered structure. In step S2, the obtained MoS 2 with a layered structure, an iron source, imidazole, benzimidazole and a raw material of an organic solvent are mixed and then a hydrothermal reaction is carried out, and the molar ratios of MoS 2 , the iron source, imidazole and benzimidazole are controlled within the above ranges, which helps to in-situ grow an iron-based metal-organic framework material on the surface of MoS 2 . After that, a calcination treatment is carried out to obtain a Fe-N-C coated MoS 2 material. Compared with directly mixing MoS 2 with an iron-based metal-organic framework material and then carrying out a calcination treatment, in-situ growth helps to improve the binding force between MoS 2 and Fe-N-C, thus helping to improve MoS 2Conductivity between Fe-N-C. Fe-N-C has high conductivity, and the Fe-N-C coating on the surface of MoS 2 helps improve the conductivity of MoS 2 . The layered structure of MoS 2 helps provide channels for rapid ion insertion and extraction, and the Fe-N-C formed from the iron-based metal-organic framework material has a porous structure, which is beneficial to the penetration of the electrolyte and ion diffusion. Adding the Fe-N-C coated MoS 2 material to the positive electrode sheet helps improve the conductivity of the positive electrode sheet and improve the ion transport performance of the positive electrode sheet. Assembling this positive electrode sheet into a secondary battery helps reduce the internal resistance of the secondary battery, thereby helping to improve the rate performance of the secondary battery.

[0122] The above are only embodiments of the present invention and are not used to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a secondary battery, characterized in that: include: S1, mixing a molybdenum source, a sulfur source, polyvinyl pyrrolidone and water and performing a synthesis reaction to obtain MoS2; S2, mixing the raw materials including the MoS2, the iron source, imidazole, benzimidazole and the organic solvent, performing a hydrothermal reaction, and then calcining the mixture under a protective gas to obtain a Fe-NC coated MoS2 material; S3, sequentially mixing, coating and rolling the Fe-NC coated MoS2 material, the positive electrode active material, the conductive agent and the binder to obtain a positive electrode sheet; S4, making the positive electrode sheet, the separator and the negative electrode sheet into a bare cell, assembling the bare cell with the outer shell and the top cover, and injecting the electrolyte to obtain the secondary battery; Wherein, the molar ratio of the MoS2, the iron source, the imidazole and the benzimidazole is (0.01~1): (0.02~0.2): (0.25~10): (0.05~2).

2. The method for preparing a secondary battery according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 140-180°C; and / or, the time of the hydrothermal reaction is 24-28h; and / or, the heating rate of the calcination treatment is 2-3°C / min; and / or, the temperature of the calcination treatment is 650-750°C; and / or, the holding time of the calcination treatment is 2-3h.

3. The method for preparing a secondary battery according to claim 1, characterized in that: The mass ratio of the Fe-NC coated MoS2 material, the positive electrode active material, the conductive agent and the binder is (0.3~1.2): (94.3~98.2): (0.5~1.5): (1~3); and / or the iron source is selected from any one or more of Fe(NO3)3·6H2O, FeCl3·6H2O and FeSO4·7H2O; and / or the organic solvent is selected from any one or more of N,N-dimethylformamide, acetonitrile and ethanol.

4. The method for preparing a secondary battery according to claim 1, characterized in that: The molar ratio of the molybdenum source, the sulfur source and the polyvinyl pyrrolidone is (0.3-1): (4-8): (0.003-0.01); and / or the temperature of the synthesis reaction is 210-220° C.; and / or the time of the synthesis reaction is 12-24 hours.

5. The method for preparing a secondary battery according to any one of claims 1 to 4, characterized in that: The number average molecular weight of the polyvinyl pyrrolidone is 10000-60000Da; and / or the molybdenum source is selected from (NH4)6Mo7O 24 ·4H2O, Na2MoO4·2H2O and (NH4)2MoS4, any one or more thereof; and / or, the sulfur source is selected from any one or more of NH2CSNH2, C2H5NS and C3H7NO2S.

6. A secondary battery comprising a positive electrode sheet, a separator, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet comprises a current collector and a positive electrode active layer, characterized in that: The materials of the positive electrode active layer include Fe-NC coated MoS2 material, positive electrode active material, conductive agent, and binder; wherein the Fe-NC coated MoS2 material is distributed on the surface of the positive electrode active material; the mass ratio of MoS2 to Fe-NC in the Fe-NC coated MoS2 material is 1:(0.2~1), the molar ratio of Fe element, N element and C element in the Fe-NC is (1~2):(2~4):(50~100), the structure of MoS2 is a layered structure, and the structure of Fe-NC is a porous structure.

7. The secondary battery according to claim 6, characterized in that: The mass ratio of the Fe-NC coated MoS2 material, the positive electrode active material, the conductive agent and the binder is (0.3~1.2): (94.3~98.2): (0.5~1.5): (1~3).

8. The secondary battery according to claim 6 or 7, characterized in that: The powder resistivity of the Fe-NC coated MoS2 material is 10 -2 ~1Ω·cm; and / or, the average pore size of the Fe-NC coated MoS2 material is 2~20nm; and / or, the porosity of the Fe-NC coated MoS2 material is 50~70%.

9. An energy storage system, comprising a unit battery, characterized in that: The unit battery is a secondary battery prepared by the method for preparing a secondary battery according to any one of claims 1 to 5 or a secondary battery according to any one of claims 6 to 8.

10. An electrical device, characterized in that: It includes the energy storage system as described in claim 9, and the energy storage system is used to provide power for the electrical equipment.

Citation Information

Patent Citations

  • An electrolytic water catalytic membrane material for preparing hydrogen for fuel cell and a preparation method thereof

    CN109167076A

  • Bimetallic nitrogen doped carbon / molybdenum disulfide composite electrocatalyst material, preparation method thereof and application thereof

    CN109499600A

  • Molybdenum disulfide / iron sulfide / nitrogen-doped carbon composite material and preparation and application thereof

    CN112928260A

  • Modification method for constructing MoS2 / NiO / TiO2 coated lithium manganese iron phosphate positive electrode material

    CN118771334A

  • MoS2-coated porous M-N-C monatomic catalyst and application thereof in lithium air battery

    CN119481104A